2017
DOI: 10.1208/s12249-017-0857-3
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Oral Bioavailability of Curcumin Using a Supersaturatable Self-Microemulsifying System Incorporating a Hydrophilic Polymer; In Vitro and In Vivo Investigations

Abstract: A supersaturatable self-microemulsifying drug delivery system (S-SMEDDS) with a reduced amount of surfactant and incorporation of a polymer precipitation inhibitor, Eudragit® E PO was developed. The optimized S-SMEDDS formulation (SS-15) consisted of 55% surfactants, 40% oils, and 5% Eudragit® E PO (curcumin at 44.4 mg/g of the formulation). The precipitation profiles from the supersaturation assay revealed that the curcumin S-SMEDDS performed as a better inhibitor of curcumin precipitation in simulated gastri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 36 publications
1
21
0
Order By: Relevance
“…In an in vivo absorption study, curcumin S-SMEDDS was diluted with distilled water and orally administered to rabbits at a dose equivalent to 50 mg/kg. Pharmacokinetics showed that the maximum concentration of curcumin obtained for S-SMEDDS was 31-fold higher than that for an aqueous suspension of curcumin [119].…”
Section: Formulations Of Curcumin Classic Dosage Form Of Curcuminmentioning
confidence: 93%
“…In an in vivo absorption study, curcumin S-SMEDDS was diluted with distilled water and orally administered to rabbits at a dose equivalent to 50 mg/kg. Pharmacokinetics showed that the maximum concentration of curcumin obtained for S-SMEDDS was 31-fold higher than that for an aqueous suspension of curcumin [119].…”
Section: Formulations Of Curcumin Classic Dosage Form Of Curcuminmentioning
confidence: 93%
“…Zhang et al [94] aimed to improve the oral absorption of baicalin, which has low solubility and poor permeability, by using a micellar formulation comprised of the carriers Pluronic P123 copolymer and sodium taurocholate. Sustained release profile of baicalin-loaded mixed micelles, in in vitro drug release experiment, held in several pH conditions, showed 14% drug released after 2 h in gastric conditions and 54% release within 48 h in intestinal conditions, compared to 34% and 79% release [105], nanoparticles [106][107][108][109][110], phytosome [111], nanoliposome [112], mixed micelles [113,114], SNEDDS [115,116], nanocarrier [117,118], nanoemulsion [119], nanosuspension [ Mixed micelles [129,130], nanoparticles [131,132], solid dispersion [133,134] , SNEDDS [135] , SMEDDS [136], lipid carrier [137], copolymeric micelles [138], exosomes [139] Naringenin DENV, HCV SNEDDS [140], solid dispersion [141], nanoparticles [142,143] , liposome [144], nanosuspension [145,146] In vitro uptake studies, carried out with a caco-2 cell line, determined the absorption of baicalin within the mixed micelles and verified their internalization ability. Baicalin-loaded ST-P123-MMs formulation achieved high oral bioavailability (Fig.…”
Section: Delivery Of Herbal Extracts and Phytochemicalsmentioning
confidence: 99%
“…191 More examples of herbal loaded NE are presented in Table 1. [192][193][194][195][196] Nanofiber It is composed of solid polymer fibers with diameters of 10-1000 nm that have a large surface area with a small pore size (Figure 13) and is prepared by the electrospinning method. 12 This novel nanocarrier has a limited role in delivering active components but with potential improvements in the therapeutic treatments and support the using of active compounds in several biomedical areas such as tissue regeneration.…”
Section: Micellementioning
confidence: 99%